Carbon-dots from babassu coconut (Orbignya speciosa) biomass: Synthesis, characterization, and toxicity to Daphnia magna. (October 2021) - Costa, Rubens S.; de Castro, Manuela O.; da Silva, Gabriela H.; Delite, Fabricio de S.; Strauss, Mathias; Ferreira, Odair P.; Martinez, Diego S.T.; Viana, Bartolomeu C.
Highlights: We present carbon nanoparticles (C-dots) obtained from babassu coconut biomass by hydrothermal carbonization. A factorial design was carried out and revealed that the synthesis parameters that showed the best fluorescence intensity were: Temperature = 230 °C; m/v ratio = 1% and Residence time = 14 h. This material is ecofriendly, uses biomass as a precursor and has no acute toxicity for the Daphnia magna model (up to 1000 mg.L −1 ). Carbon dots were shown to be sensitive to Fe 3+, Co 2+, Ni 2+, Cu 2+, Zn 2+ and Cd 2+ ions, with their fluorescence suppressed in their presence. Abstract: The present study provides amethodology for the synthesis of carbon dots through hydrothermal carbonization of the babassu coconut (Orbignya speciosa) mesocarp as a precursor matrix. The synthesis parameters (temperature, residence time and% m/v) were studied through a factorial design with the fluorescence intensity as determining factor in choosing the best sample. Particles with diameters in the range of 2.4 - 47.7 nm were obtained, which presented two emission regions, one at approximately 467 nm ( λ E X  =  370 nm) and the other at approximately 550 nm ( λ E X  = 470 nm). These carbon dots showed the phenomenon of suppression of fluorescence when in the presence of Fe 3+, Co 2+, Ni 2+, Zn 2+, Cu 2+ and Cd 2+ ions, exhibiting good linearity in the fluorescence decay according to the concentration of ions in the medium, indicating potential application as a sensor for these ionic species. Acute toxicity testing with Daphnia magna model demonstrated absence of toxic effect (immobility) of the carbon dots to this aquatic organism bioindicator after 48 h of exposure, even at high concentrations (up to 1000 mg.L −1 ). Graphical abstract: Image, graphical abstract